Tindak Pidana Pencucian Uang Melalui Perbankan di Indonesia - Sitanggang, Tikkos; Zein, Subhan; Sudarto, Sudarto (LITERATUS, 2025)
This thesis analyzes the crime of money laundering (TPPU) through banking in Indonesia, with a focus on the implementation of Law No. 8/2010 and the judge's consideration in Decision No. 208/PID.SUS/2018/PT.DKI. The background of this research includes the increase in money laundering crimes triggered by technological advances and globalization, which makes it easier for perpetrators to hide the origin of illegal funds. This research identifies various challenges in the implementation of the law, including the limited authority of relevant institutions, regulations in the banking sector, and constraints in inter-agency cooperation. In addition, this research also evaluates the judges' considerations in decisions relating to the defendant's role in money laundering crimes. The results show that although the law is in place, the effectiveness of law enforcement still needs to be improved through improved regulation and cross-sector cooperation. The follow of the money method in handling Money Laundering Crimes has significant benefits, especially in dismantling financial crime networks.